TEKNOLOGI PRODUKSI SAYURAN ORGANIK - Situmeang, Yohanes Parlindungan; Udayana, I Gusti Bagus (dwijenAGRO, 2012)
Organic vegetables can be cultivated, both in the lowlands and highlands. Organic vegetables are: spinach, kale, cabbage, broccoli, green beans, carrots, potatoes, peas, peppers, tomatoes, cabbage, lettuce, scallions, and others. However, organic vegetable production can not meet people's needs in terms of quantity, quality, and continuity.Preparation of guidelines for organic vegetable production aims to provide a general guide to implement organic cultivation of vegetables in accordance with the applicable standards so that the resulting product can actually be accounted for, qualified, competitive, safe for consumption, environmentally friendly and sustainable.Application of organic farming must follow the rules completely correct according to Standard Operating Procedures (SOP) norm-based farming is good and right (Good Agriculture Practices / GAP), with several activities, namely: site selection, land conversion, manufacture of organic fertilizer, pesticide manufacture of plant, land preparation, seed preparation, seeding, planting, fertilizing, watering, thinning, crop protection and harvesting.Keywords: Technology, Production and Organic Vegetables